Impact of COVID-19 Pandemic on Mental Health of Health Care Workers and Its Determining Factors: A Systematic Review - Bhatta, Nikita; Shah, Sangam; Sah, Sanjit Kumar; Paudel, Basanta Sharma (Journal of Karnali Academy of Health Sciences, 2020)
Background: Since the outbreak of COVID-19, the global pandemic has taken a toll on the mental well-being of people around the world, especially health care workers. Health care workers have a heavy work burden and are compelled to isolate themselves. Their mental health has worsened with increased symptoms of anxiety and depression affecting their quality of life. This review aims to identify the magnitude of psychological distress in health care workers and their major contributing factors during the COVID-19 pandemic for strengthening their mental health in the present and upcoming pandemics.Methods: The search databases such as ScienceDirect, Embase, Cochrane Library, PubMed, and Google scholar were used for finding favorable studies. The search was conducted until 16th May 2020, and articles from 1st February 2020 to 20th April 2021 were included in the review.Results: A total of 2879 articles were identified and 18 studies were selected for the review. The psychological impact in the studies-anxiety and depression were prevalent in range from 10-90 percentage of total participants. Insomnia and stress were also commonly reported with maximum prevalence of 98.5% of total participants. These impacts were often associated with nursing profession and females, further aggravated by inadequate personal protective equipment, stigmatization and self-isolation.Conclusion: Various mediators such as female gender, young adulthood, comorbidity, nursing profession, previous history of mental illness, stigmatization, and employment in high risk areas, heavy workload, and poor infection control practices are major contributing factors for poor mental outcome in health care workers during COVID-19 pandemic.